2011
DOI: 10.1021/ja207458b
|View full text |Cite
|
Sign up to set email alerts
|

Water- and Ionic-Liquid-Soluble Branched Polythiophenes Bearing Anionic and Cationic Moieties

Abstract: The synthesis of ionically functionalized branched polythiophenes with either carboxylic acid (anionic, P3T-COOH) or methylimidazolium (cationic, P3T-MIM) end groups is presented. Due to the large number of end groups present in the polymer, the functionalization has a major impact on the solubility of the polymers. In the case of P3T-COOH, the polymer shows a fully reversible phase transfer between organic solvents and water, depending on the pH. Remarkably, the ionic-liquid-modified polymer P3T-MIM is solubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…For the aqueous IL at 20 8C, the typical peaks at d = 8.67, 7.45, and 7.35 ppm could be assigned to C(2)ÀH and C (4,5)ÀH of the imidazolium ring, while the peaks at d = 3.82 and 3.59 ppm could be assigned to hydrogen atoms of CH 3 and (CH 2 CH 2 O) n of the PEG chain, respectively. Here, the chemical shifts were reported with reference to residual water resonance at d = 4.69 ppm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the aqueous IL at 20 8C, the typical peaks at d = 8.67, 7.45, and 7.35 ppm could be assigned to C(2)ÀH and C (4,5)ÀH of the imidazolium ring, while the peaks at d = 3.82 and 3.59 ppm could be assigned to hydrogen atoms of CH 3 and (CH 2 CH 2 O) n of the PEG chain, respectively. Here, the chemical shifts were reported with reference to residual water resonance at d = 4.69 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al [1d] demonstrated a reversible phase transfer of a-cyclodextrincoated gold nanoparticles between aqueous and toluene phases, and it could be controlled by UV-visible light. Tang et al[2b] reported a reversible phase transfer of CdTe nanoparticles between aqueous and toluene phases driven by temperature, and Ludwigs et al [4] found that polythiophenes with a carboxylic acid group could reversibly transfer from the water phase to a mixture of THF and CHCl 3 by adjusting the pH value of the solution.In the last two decades, ionic liquids (ILs) have been found widespread applications in chemical synthesis, [5] materials preparation, [6] biomass dissolution, [7] gas capture, [8] energy production, [9] and separation science [10] because of their unique properties, [11] such as ultralow vapor pressure, wide liquid temperature range, nonflammability, high stability, and tunable structure and property. Many efforts have been made to realize product separation from IL-based solvents by means of pressure, [12] temperature, [13] and CO 2 .…”
mentioning
confidence: 99%
“…The conjugated BILs exhibit characteristics of both conjugated polymers and polyelectrolytes, which implies potential applications in dye-sensitized solar cells and electrochemical devices. [10] Mülhaupt and co-workers developed new families of BILs with onion-like topology, containing a core of hyperbranched poly(1,3-diether), a polar inner imidazolium cation shell, and an nonpolar outer n-alkyl shell. BILs are very effective phase-transfer systems, and they enable extraction of water-soluble dyes and nanomaterials from an aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, conjugated polymers from the organic material group are widely used for various sensing applications. Among these, poly(thiophene) (PTh) and its derivatives have received great attention as sensing materials, particularly for DNA [2], gas [3], glucose oxidase (GOX) [4], ion chromatism [5], magnetometer [6] and pH [7]. In previous studies, we presented a synthetic mechanism of pristine PTh nanoparticles [8], a size controlling process [8], a kinetic mechanism of PSt/PTh core/shell nanoparticles [9], the control of fluorescence properties by varying the PTh shell thickness of the PSt/PTh core/shell nanoparticles [10], and a new composite mechanism and properties of hybrid Fe 3 O 4 NPs-PSt/PTh composite nanoparticles [11].…”
Section: Introductionmentioning
confidence: 99%